OCRL1 Modulates Cilia Length in Renal Epithelial Cells - Rbaibi, Youssef (2012)
Lowe syndrome is an X-linked disorder characterized by cataracts at birth, mental retardation and progressive renal malfunction that results from loss of function of the OCRL1 (oculocerebrorenal syndrome of Lowe) protein. OCRL1 is a lipid phosphatase that converts phosphatidylinositol 4,5-bisphosphate to phosphatidylinositol 4-phosphate. The renal pathogenesis of Lowe syndrome patients has been suggested to result from alterations in membrane trafficking, but this cannot fully explain the disease progression. We found that knockdown of OCRL1 in zebrafish caused developmental defects consistent with disruption of ciliary function, including body axis curvature, pericardial edema, hydrocephaly and impaired renal clearance. In addition, cilia in the proximal tubule of the zebrafish pronephric kidney were longer in ocrl morphant embryos. We also found that knockdown of OCRL1 in polarized renal epithelial cells caused elongation of the primary cilium and disrupted formation of cysts in three-dimensional cultures. Calcium release in response to ATP was blunted in OCRL1 knockdown cells, suggesting changes in signaling that could lead to altered cell function. Our results suggest a new role for OCRL1 in renal epithelial cell function that could contribute to the pathogenesis of Lowe syndrome.